2004
DOI: 10.1002/pssc.200304434
|View full text |Cite
|
Sign up to set email alerts
|

Structural and magnetic studies of 1% Ho:Gd 0.99−x Lu x alloys

Abstract: We present a study of the magnetic and structural properties of 1% Ho:Gd 0.99-x Lu x alloys. X-ray diffraction patterns for 1% Ho:Gd 0.99-x Lu x (x = 0.01, 0.39, and 0.59) show a single hexagonal type phase structure and the lattice parameters are found to depend on the Lutetium concentration. Magnetic measurements were made at temperatures between 100 K and 850 K using a vibrating sample magnetometer with a maximum field of 13.5 kOe. All the samples under investigation show a ferromagnetic behavior up to Curi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…This study added a new detail to the phase diagram and revealed the existence of Ferro-I in addition to helical antiferromagnetic and canted ferromagnetic phases. Recently, we studied the magnetic and structural properties of Gd 0.99Àx Lu x Ho 0.01 and found that these alloys have single hexagonal type phase structure and the lattice parameters are found to depend on the Lutetium concentration [11]. We also found that the Curie temperature and the saturation magnetization decrease with increasing Lutetium concentration.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…This study added a new detail to the phase diagram and revealed the existence of Ferro-I in addition to helical antiferromagnetic and canted ferromagnetic phases. Recently, we studied the magnetic and structural properties of Gd 0.99Àx Lu x Ho 0.01 and found that these alloys have single hexagonal type phase structure and the lattice parameters are found to depend on the Lutetium concentration [11]. We also found that the Curie temperature and the saturation magnetization decrease with increasing Lutetium concentration.…”
Section: Introductionmentioning
confidence: 94%
“…This study is part of a project on rare earth alloys using different techniques such as XRD, VSM, FMS and NMR [3,11].…”
Section: Introductionmentioning
confidence: 99%